Structural optimisation of discontinuous carbon fibre composites - Qian, Connie Cheng (2014)
There has been a growing interest in using discontinuous carbon fibre composites for semi-structural applications within the automotive industry. The main advantages of discontinuous fibres are low material costs, low wastage and low touch labour compared with processes using carbon fibre textiles. Directed Carbon Fibre Preforming (DCFP) is an automated process for producing complex 3D preforms for liquid moulding. DCFP offers the potential for producing highly optimised structures, with local control over tow size, fibre length and volume fraction within the component. The execution of this is challenging however, as confidence in the current library of material properties is low and existing structural optimisation packages only consider a very limited number of design variables, which are restricted to more conventional composite materials. This thesis aims to establish a structural design tool to exploit the design freedom offered by the DCFP process. A large number of parameters associated with the fibre architecture can be controlled to meet a range of design criterions such as performance, weight and cost. The optimisation tool is capable of generating locally varied fibre areal mass and thickness maps that are suitable for manufacture by the robot controlled process. The developed model adopts a multi-scaled finite element approach. Meso-scale simulations are performed to establish size effects in discontinuous fibre composites, to quantify the level of stochastic variability and to determine the representative volume element for a given fibre architecture. A DCFP material database is generated to facilitate macro-scale modelling at the component level. The macro-scale model iteratively redistributes material in order to minimise the total strain energy of the model under prescribed loading conditions. The optimised model is segmented into areas of uniform areal mass, where the zone geometries are tailored to achieve representative material properties according to the meso-scale results, whilst ensuring the design is fit for manufacture. An automotive spare wheel well has been chosen as a demonstrator component, enabling two DCFP architectures to be compared against a continuous glass/carbon fibre NCF design. The first case offers a high performance (high specific stiffness) solution and the second offers a low cost option using high filament count tows. Following optimisation, results suggest that a 3K 25mm fibre length DCFP option can achieve a specific stiffness 52% higher than the glass/carbon baseline design, but for 1.33 times higher material cost. Alternatively, the specific stiffness of a 24K 50mm fibre length DCFP is marginally lower than the first option, but still out-performs the baseline for just 67% of the material cost. The structural optimisation method demonstrates that discontinuous fibre composites can compete against continuous fibre counterparts for semi-structural applications.